Wide spread arsenic in deeper groundwater of western Bengal basin, West Bengal, India: Implications for sustainable alternate drinking water sources - Mukherjee, Abhijit; Fryar, A.; Scanlon, B.; Bhattacharya, P.; Thunvik, R.; Bhattacharya, A. (2012)
Availability of safe drinking water is a major concern in the delta plains of the major Himalayan-Tibetan rivers in southern and southeastern Asia. While indiscriminate use of rivers and other surface water bodies for disposal of sewage and industrial waste has rendered them non-potable, natural, non-point source, elevated Arsenic (As) concentrations in groundwater exceeding the World Health Organization's (WHO) guideline value for drinking water of 0.01 mg/L have put millions of people at risk. Hence, finding an alternate, suitable and sustainable drinking-water source has been a priority in these areas. Generally, higher concentrations of dissolved As are found in groundwater of shallower aquifers and several studies have advocated deeper aquifers as a possible safe substitute. Using a composite hydro-geological approach, we demonstrate that regional-scale deeper groundwater As contamination in the western Bengal basin is dependent on the aquifer-aquitard framework and complex redox processes with partial equilibrium under natural flow conditions. Widespread deep irrigation pumping may be drawing shallower, contaminated groundwater down to greater depths. These findings have severe implications on finding alternate drinking water sources, in West Bengal, and adjoining areas of Bangladesh, with plausible similar geological and hydrogeological framework. © 2012 Taylor & Francis Group.